Comparing Professional Identities, Attitudes, and Views in Public Communication: A Study of Chilean Journalists and Public Relations Practitioners - Mellado-Ruiz, C (2011)
Public relations (PR) practitioners and journalists professional views and attitudes toward each other have been a subject of academic inquiry during the past decades; however, much of this research has focused on Europe and North America. In other regions of the world, for example in Latin America, historical developments and social understandings have led to slightly different conceptualizations of PR and journalism. Using Chile as a case study, this paper reports the results of an examination of Chilean journalists and PR practitioners professional conceptions. While both groups tend to have somewhat similar views of media relations and see themselves as part of the same profession, there are also important differences which are most likely based on professional socialization processes rather than educational backgrounds or sociodemographic and work related variables. Implications for contextually grounded approaches to the study of PR and journalism are highlighted. © 2011 Elsevier Inc.
Keywords: Journalism; Journalists; Public relations; Public relations practitioners; Professional identity; Media relations